EVALUATION OF RTH IN REGIONAL SPATIAL PLAN WITH NDVI IN KENDARI CITY - Septianto Aldiansyah (Tunas Geografi, 2021)
Kendari City is the capital of Southeast Sulawesi Province with a population of 345,110 people. The number of residents can trigger a narrowing of RTH (RTH) due to meeting the need for land over time. RTH in urban areas ideally is 30% of the total area with 20% public RTH and 10% private RTH. This study aims for RTH based on the comparison of the area of the RTH Regional Spatial Plan (RTRW) and the actual RTH, the population, the ability to produce oxygen (O2) and absorption of carbon dioxide (CO2) in the actual RTH. This research uses quantitative descriptive research in evaluating RTH. The results showed that public RTH in the RTRW still lacked 6.93% so that it was still necessary to review the RTRW to meet these needs. The current RTH is also still less than the minimum standard of RTH in Kendari City of 7.01% in public RTH. If it is accumulated, the current availability of RTH still does not meet the minimum standard of RTH in Kendari City. The availability of oxygen (O2) and absorption of carbon dioxide (CO2) in Kendari City can still meet the needs of residents in Kendari City.